Significance of Siddha Thirithoda Balancing Food Stuffs (International Journal of Ayurveda and Pharma Research, 2022)
The Siddha system of medicine is an ancient medical system, which provides ‘Holistic Health’. The word ‘Siddha’ originated from the  word ‘Siddhi’ meaning achievement of perfection, eternal bliss and accomplishment. The Siddha system evolved based on ninety-six tools (96 Thattuvam) which include physical, physiological, psychological and intellectual aspects of every human being. Among the 96 tools, the five elements i.e. Pancha bootham namely Earth, Water, Fire, Air and Space are the fundamental units of everything in the human body and the cosmos. There are three vital life factors (Vaatham, Pittam, Kabham) responsible for good health. There is a relationship between these to maintain the body’s healthy. Any increase or decrease in humour causes diseases. Thirthoda sama porutkal (TSP) maintains these humour when we are using our regular diet. This article details the TSP to maintain the body healthy.